Plastics packaging : properties, processing, applications, and regulations - Selke, Susan E. M.; Culter, John D., 1937-; Auras, Rafael; Rabnawaz, Muhammad (Hanser Publishers ; Hanser Publications, 2021)
"Plastic materials continue to play a vital and growing role in packaging applications. It is thus more important than ever that all involved in the packaging industry command a basic understanding of the properties of the common packaging plastics. This highly regarded book provides just that to students and packaging professionals alike: material properties and how they relate to the chemical structure of the polymers, common processing methods for packaging applications, help with writing specifications, designing, fabricating, testing, and controlling the quality of the plastic material are covered comprehensively. The fourth edition has major revisions in discussions of sustainability, recycling, and design for sustainability. Coverage of biodegradable and biobased plastics is also increased. Discussion of coatings is also expanded. Further updates and enhancements throughout ensure Plastics Packaging remains an indispensable resource for both the packaging expert and the novice."--